Risk Minimization Measures in Off-Label Drug Use: A Survey of Community Pharmacists in Malaysia - Fatokun, Omotayo (Current Drug Safety, 2020)
Background: While off-label drug use is common and sometimes necessary, it also presents considerable risks. Therefore, measures intended to prevent or reduce the potential exposure to off-label risks have been recommended. However, little is known about community pharmacists’ beliefs regarding these measures in Malaysia. Objectives: This study examined community pharmacists’ beliefs towards risk minimization measures in off-label drug use in Malaysia and assessed the relationship between perceived risk of off-label drug use and beliefs towards risk minimization measures. Methods: A cross-sectional survey was conducted among 154 pharmacists practicing in randomly selected community pharmacies in Kuala Lumpur and the State of Selangor, Malaysia. Results: The majority agreed or strongly agreed that adverse drug events from the off-label drug should be reported to the regulatory authority (90.9%) and the off-label drug should only be used when the benefit outweighs potential risks (88.3%). Less than half (48.1%) agreed or strongly agreed that written informed consent should be obtained before dispensing off-label drugs and a majority (63.7%) agreed or strongly agreed that the informed consent process will be burdensome to healthcare professionals. Beliefs towards risk minimization measures were significantly associated with perceived risk of off-label drug use regarding efficacy (p = 0. 033), safety (p = 0.001), adverse drug rection (p = 0.001) and medication errors (p = 0.002). Conclusion: The community pharmacists have positive beliefs towards most of the risk minimization measures. However, beliefs towards written informed consent requirements are not encouraging. Enhancing risk perception may help influence positive beliefs towards risk minimization measures.
Keywords: risk perception